2020
DOI: 10.1039/d0sc00070a
|View full text |Cite
|
Sign up to set email alerts
|

On/off porosity switching and post-assembly modifications of Cu4L4 metal–organic polyhedra

Abstract: Synthetic porous materials composed of metal-organic polyhedra (MOPs) have found application in topical areas such as gas storage, separation and catalysis. Control over their physical properties (e.g. porosity) has typically been achieved through ligand design or judicious choice of metal ions. Here, we demonstrate pore-size control and on/off porosity in Cu 4 L 4 MOPs by exploiting their structural non-rigidity. We report an aldehyde-functionalised MOP (1) that can be isolated in five distinct solvatomorphs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…Structural transformations of MOCs can be induced by many factors, as recently reviewed. [102] Structures can adapt as a result of changes in solvent, [103] concentration, [104] temperature, [105] light, [106] and guest binding. [68] The postassembly modification of MOCs via new covalent bond formation is a particularly active area.…”
Section: Structural Transformationsmentioning
confidence: 99%
“…Structural transformations of MOCs can be induced by many factors, as recently reviewed. [102] Structures can adapt as a result of changes in solvent, [103] concentration, [104] temperature, [105] light, [106] and guest binding. [68] The postassembly modification of MOCs via new covalent bond formation is a particularly active area.…”
Section: Structural Transformationsmentioning
confidence: 99%
“…Owing to solubility of 1 in DMF and DMA, we explored whether other crystallisation conditions can lead to a different crystal-packing through solvatomorphism, ( Bloch et al, 2020 ; Deegan et al, 2021 ). Indeed, slow vapour diffusion of diisopropyl ether (DiPE) into a DMA solution of the cage yielded crystals of 2 after 4 days.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we found that post-assembly imine condensations can be carried out on Cu 4 L 4 MOCs using a Sc(OTf) 3 catalyst under mild conditions. ( Bloch et al, 2020 ; Matsumoto et al, 2017 ). Thus, we employed the same conditions for the covalent cross-linking of 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations